Characterizing two models for abortion care in Argentina pre-Law 27.610: 2016-2019 - Erika E. Atienzo; Belén Grosso; Ruth Zurbriggen; David Zambrano; María Vivas; Brianna Keefe-Oates; Caitlin Gerdts; Alexandra Wollum (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE Explore the use of two abortion care models in Argentina over the period 2016-2019: pro-rights private medical service providers and abortion accompaniment (via self-management and via health institutions); and compare the profile of who accesses these models and when. METHODS We used data from accompaniment collectives in the Socorristas en Red and private service providers. We estimated annual abortion rates via these service models and compared the profile of the populations by type of service and gestational age (2019) using descriptive statistics and chi-square tests. RESULTS In 2016, 37 people per 100,000 women of reproductive age obtained accompanied self-managed abortions, and the number increased to 111 per 100,000 in 2019, a threefold increase. The rate of abortions via care providers was 18 per 100,000 in 2016 and 33 in 2019. Higher proportions of those who obtained abortion via care providers were 30 years or older. A higher proportion of those accompanied were 19 years or younger; 11% of those who obtained accompanied self-managed abortions were more than 12 weeks gestation compared with 7% among those who had accompanied abortions via health institutions and 0.2% among those who had abortions with private providers. A higher proportion of those who accessed accompanied abortions after 12 weeks gestation had lower educational levels, did not work or have social security coverage, had more past pregnancies, and attempted to terminate their pregnancies prior to contacting the Socorristas compared to those who had accompanied abortions at 12 weeks or earlier. CONCLUSIONS In Argentina, prior to Law 27.610 models of care guaranteed access to safe abortion. It is important to continue making visible and legitimizing these models of care so that all those who decide to have an abortion, whether inside or outside health institutions, have safe and positive experiences.